Improving Students’ Speaking Ability Through Loora As Mobile-Assisted Language Learning Application - Dimas; Daulay, Ernita (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study was prompted by the importance of technology in language learning, especially in improving students' speaking abilities. One of the technologies used is the Loora application, a mobile-based language learning (MALL) application that uses AI to provide automatic feedback and simulate everyday conversations. This study investigates how the Loora application improves students' speaking ability. The study population was 9th-grade students at MTs Al-manar in Deli Serdang, North Sumatra, with a sample of 20 students selected through purposive sampling. The research method used was classroom action research, which consisted of two cycles. Data collection was conducted through a pre-test as a diagnostic test, and a post-test was conducted each cycle to measure the improvement of students' speaking ability and interviews to understand students' experience using this application. The results showed a significant improvement in accuracy (pronunciation, vocabulary, and grammar) and speaking fluency. The highest increase occurred in the vocabulary aspect, with a percentage increase of 38.49%, followed by grammar by 22.05% and pronunciation by 17.72%. Meanwhile, speaking fluency increased by 17.57%. From the analysis, the accuracy aspect experienced a higher increase than fluency, where the accuracy score increased by 21.22% and fluency by 17.57%. The interview results confirmed the students' improved speaking skills and highlighted their favorable experiences with the Loora app. They felt more confident in speaking after using Loora, and they appreciated the automatic feedback feature that helped them correct mistakes and better understand English. This positive experience underscores the app's user-friendliness, which is encouraging for both educators and app developers. This research shows that the Loora application can be a learning media that significantly improves students' speaking abilities. Educators are advised to consider using MALL-based technology when teaching languages, as it can enhance students' speaking ability. These findings can potentially be used by application developers to increase the interactive elements of their language learning apps, hence increasing their potency in developing students' speaking abilities.